Uma contribuição à definição de indicadores de desempenho de instituições federais de educação tecnológica do Brasil na abordagem do balanced scorecard - Silva, Cleide Maria Rodrigues Clímaco Costa e (2008)
This Master of Science Thesis deals with a study on applying the BSC Balanced Scorecard to assess the performance of Federal Centers for Technological Education Institution in Brazil, the CEFET s (Centro Federal de Educação Tecnológica), government organizations non for profit. It s accomplished a literature review in order to understand the BSC and its application to non for profit organizations and as a main result it is proposed a BSC conceptual model with an inversion of the main BSC perspective from financial to customer/society. Taking the FORPLAN/CONCEFET performance indicators matrix it is developed a set of performance indicators for the two tops perspective in the conceptual model proposed five for customer/society perspective and three for financial/budget perspective. A field survey with ten CEFET s General Directors is conducted to validate the indicators and assess the perception of the Directors on the hierarchy of the conceptual model, and a hierarchy among the indicators as well. The main results suggests that the indicators are validated, that most of the Directors support the hierarchy presented in the conceptual model but 30% of them have a traditional model with financials coming first. In terms of indicator hierarchy, there s a slight priority for the student unitary cost among the financial perspective indicators, and a relative balance among the customer/society perspective indicators